Scientific Exegesis of QS. An-Nahl 68–69 on bees: Integrating Qur’anic Interpretation and Modern Scientific Findings - Astiwi Sara; Ahmad Zuhri; Nuraisah Simamora; Insan Akbar (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2025)
This study conducts a scientific exegesis (Tafsir ‘ilmi) of Qur’an 16:68-69, which describes divine inspiration bestowed upon honeybees and the production of a healing drink from their abdomens. Using a descriptive-analytical qualitative approach and the tahlil method, classical and modern interpretation sources were integrated with contemporary findings in apidology and apitherapy. Major exegetes (Ibn Kathir, al-Tabari, al-Qurtubi, Saayid Qutb, Tantawi Jauhri, et al.) Unanimously interpreted “awha” as divinely instilled instinct accurately anticipating modern discoveries of hexagonal hive geometry, waggle dance communication, and age based polytheism. Scientific evidence confirms that bee products (honey, royal jelly, propolis, pollen, venom, beeswax) contain bioactive compounds with proven antioxidant, antibacterial, anti-inflammatory, immunomodulatory, and wound-healing properties for validating the Qur’anic claim of “healing for people” (Syifaul linnas). The findings illustrate profound harmony between seventh-century revelation and twenty-first-century biology and medicine, affirming the Qur’an’s role as both theological guidance and empirically verifiable natural observation while underscoring bee’s ecological and therapeutic significance.